2009
DOI: 10.1007/978-3-642-10841-9_19
|View full text |Cite
|
Sign up to set email alerts
|

Contract Auctions for Sponsored Search

Abstract: Abstract. In sponsored search auctions advertisers typically pay a fixed amount per click that their advertisements receive. In particular, the advertiser and the publisher enter into a contract (e.g., the publisher displays the ad; the advertiser pays the publisher 10 cents per click), and each party's subjective value for such a contract depends on their estimated click-through rates (CTR) for the ad. Starting from this motivating example, we define and analyze a class of contract auctions that generalize th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 17 publications
(20 reference statements)
1
7
0
Order By: Relevance
“…This also illustrates the main differences from a paper using the QVA for sponsored search [9]. There, under the condition of consistent valuations, which is implied by our weakly transferable utility condition, it is also shown that the QVA is strategy-proof.…”
Section: Related Worksupporting
confidence: 52%
See 2 more Smart Citations
“…This also illustrates the main differences from a paper using the QVA for sponsored search [9]. There, under the condition of consistent valuations, which is implied by our weakly transferable utility condition, it is also shown that the QVA is strategy-proof.…”
Section: Related Worksupporting
confidence: 52%
“…We believe that techniques that successfully address these issues could be effectively used in many real-world settings, ranging from the assignment of programming and development tasks in open-source projects, sponsored search [9], incentivizing privacy in e-commerce [4], to allocating an infrastructural project with a fixed budget to one of a number of competing construction companies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to reduce the effects of divergence in valuations, Goel et al have introduced contract auctions, which generalize the classical second price auction [40]. In particular, they propose an impression-plus-click pricing mechanism, in which advertisers pay a fixed amount per impression plus an additional amount if their ad is clicked.…”
Section: Click-through-rate Estimationmentioning
confidence: 99%
“…A hybrid mechanism similar to what we suggest has been defined and studied in [7,8], under the name impression plus click pricing: the equivalence result is not satisfied there because the beliefs about the CTR are considered potentially different between the publisher and the advertiser, hence the need for a richer mechanism. An interesting feature of the proposed auction scheme is that despite the relaxation of this common knowledge assumption, the mechanism is still incentive-compatible.…”
Section: Introductionmentioning
confidence: 99%